Body size changes in elite junior rowers: 1997 to 2007 - Rakovac, M.; Smoljanovic, T.; Bojanic, I.; Hannafin, J. A.; Hren, D.; Thomas, P. (Collegium Antropologicum, 2011)
The aim of this study was to determine whether elite international junior rowers in 2007 were heavier and taller than those evaluated in 1997, and to compare this change among finalists and non-finalists, and sweep rowers and scullers. Body weight and height data obtained by a questionnaire from a total of 398 rowers (42% female, 58% male) at the Junior World Rowing Championships in Beijing, People`s Republic of China, in 2007 (65.9% of all competitors), were compared with data from 603 rowers measured at the Junior World Rowing Championships in Hazewinkel, Belgium in 1997 (36.5% female, 63.5% male, representing 90% and 89% of all competitors, respectively, by gender). Male and female rowers in 2007 were significantly taller compared to those in 1997 (1.0 cm, p=0.009 and 2.1 cm, p<0.001, respectively; one-sample t-test). No statistically significant difference was found for body mass. The finalists and sweep rowers were taller and heavier compared to nonfinalists and scullers at both Championships respectively. The heights of elite level junior rowers increased significantly over the decade. The finalists at World Junior Rowing Championships were again taller and heavier compared to the nonfinalists.